2014
DOI: 10.1177/0891988714532020
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and Neuropsychiatric Prediction of Global Cognitive Status Among Older Spanish-Speaking Hispanics and English-Speaking Whites

Abstract: Background Neuropsychological and depression measures have been found to predict cognitive functioning. We compared these associations among whites and Spanish-speaking Hispanics. Methods Fifty-two pairs of whites and Hispanics were matched demographically and clinically in a cross-sectional study. Hierarchical regression analyses predicted Global Deterioration Scale (GDS) rating by baseline neuropsychological tests and depression symptoms. Results Neuropsychological tests predicted GDS better in whites; d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
2
2
0
Order By: Relevance
“…Individuals with greater cognitive reserve may also perform at a higher level on cognitive tests and functional measures, than would otherwise be expected for the severity of their underlying neurodegenerative or vascular brain disease. In this study, no difference in cognitive reserve between the two ethnic groups would be expected, based on our findings that no statistical difference in age and education level was present between the Hispanic and WNH participants within each diagnostic group, a finding consistent with other studies (Espino et al, 2004; Gasquoine, 1999; Guerrero-Berroa et al, 2014, 2016; Uzzell, Ponton, & Ardila, 2013). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Individuals with greater cognitive reserve may also perform at a higher level on cognitive tests and functional measures, than would otherwise be expected for the severity of their underlying neurodegenerative or vascular brain disease. In this study, no difference in cognitive reserve between the two ethnic groups would be expected, based on our findings that no statistical difference in age and education level was present between the Hispanic and WNH participants within each diagnostic group, a finding consistent with other studies (Espino et al, 2004; Gasquoine, 1999; Guerrero-Berroa et al, 2014, 2016; Uzzell, Ponton, & Ardila, 2013). …”
Section: Discussionsupporting
confidence: 90%
“…Studies comparing White non-Hispanics (WNHs) to ethnic minorities on tests of cognitive performance among individuals with dementia have consistently shown lower scores in memory, executive function, and overall cognitive performance among Hispanics, even when controlling for factors such as age, sex, education, and socioeconomic status (Boone, Victor, Wen, Razani, & Pontón, 2007; Castora-Binkley, Peronto, Edwards, & Small, 2015; Espino & Lewis, 1998; Espino, Lichtenstein, Palmer, & Hazuda, 2004; Gasquoine, 1999; Guerrero-Berroa et al, 2014, 2016). Among the elderly, one explanation for these differences in cognitive performance could be the greater reported prevalence of neurodegenerative disease, such as Alzheimer’s disease (AD).…”
Section: Introductionmentioning
confidence: 99%
“…In the general elderly population, the association between neuropsychiatric symptoms (and in particular depressive symptoms) and cognitive impairment/ decline including dementia has been robustly found [ 1, 2 ]. This association has been reported in the elderly from different ethnic backgrounds [ 3 ] and has been supported by neuropathological findings [ 4, 5 ]. However, longitudinal studies have reported an association that affects only men [ 6 ] or those with higher educational attainment [ 7 ].…”
Section: Introductionsupporting
confidence: 81%
“…The lack of report of the effect sizes of the association make comparisons of these results with those of other studies challenging. One cross-sectional study with a small sample ( n = 52 white non-diabetic older adults) reported larger effect sizes (correlations ranging from 0.311 to 0.497) for the associations between depressive symptoms (as measured by the total score or two individual items from the Hamilton Depression Rating Scale) [ 38 ] and cognitive status, after controlling for demographics [ 3 ].…”
Section: Discussionmentioning
confidence: 99%